Odpowiedzi

2010-04-07T14:40:42+02:00
A₁=b₁=5
a₃=b₄
a₅=b₁₆

a-geo, b-aryt

a₇? b₅?

a₃=a₁q²=5q²
a₅=a₁q⁴=5q⁴

b₄=b₁+3r=5+3r
b₁₆=b₁+15r=5+15r

a₇=a₁q⁶=5q⁶

b₅=a₁+4r

5q²=5+3r |*(-5)
5q⁴=5+15r

-25q²=-25-15r
5q⁴=5+15r

5q⁴-25q²=-20 |:5
q⁴-5q²+4=0
q²=t
t²-5t+4=0
Δ=25-16=9=3²
t₁=[5+3]/2=4
t₂=[5-3]/2=1

q²=1 lub q²=4
q=1 lub q=-1 lub q=2 lub q=-2

q=1 lub q=-1
r=0
a₇=5
b₅=5

q=2 lub q=-2
20=5+3r
15=3r
r=5
a₇=5*2⁶=5*64=320
b₅=5+5*4=25
Najlepsza Odpowiedź!
2010-04-07T14:46:05+02:00
W ciągu arytm:

bn = b1+(n-1)*r

w ciągu geom:
an = a1 *q ^(n-1)

dodatkowo:
a1=b1=5
a3=b4
a5=b16

podstawiamy:
a1=b1=5, czyli:
bn = 5+(n-1)*r
an = 5 *q ^(n-1)

a3=b4, czyli
5 *q ^(3-1) = 5+(4-1)*r
5 *q ^2= 5+ 3*r

a5=b16
5 *q ^(5-1) = 5+(16-1)*r
5 *q ^4= 5+ 15*r

tworzymy układ układ równań:
5 *q ^2= 5+ 3*r -------> r= (5 *q ^2- 5)/3
5 *q ^4= 5+ 15*r

podstawiamy do drugiego równania:
5 *q ^4= 5+ 15*(5 *q ^2- 5)/3
5 *q ^4= 5+ 25 *q ^2- 25 dzilimy przez 5
q ^4 - 5 *q ^2 + 4 =0

za q ^2 podstawiamy t:
t^2 - 5 *t + 4 =0

delta = 25 - 16 = 9
pierwiastek (delta ) = 3

t=(5 - 3)/2 = 1 lub t=(5 + 3)/2 = 4

stąd:
q ^2 = 1 lub q ^2 = 4
q = 1 lub q = -1 lub q = 2 lub q = -2

dla q = 1 lub q = -1:

r= (5 *q ^2- 5)/3 = 0

b5 = 5+4*0 = 5
a7 = 5 *q ^6 = 5

dla q = 1 lub q = -1:

r= (5 *q ^2- 5)/3 = 0

b5 = 5+4*0 = 5
a7 = 5 *q ^6 = 5

dla q = 2 lub q = -2:

r= (5 *q ^2- 5)/3 = 5

b5 = 5+4*5= 25
a7 = 5 *q ^6 = 5 * 64 = 320